Doxorubicin-reinforced supramolecular hydrogels of RGD-derived peptide conjugates for pH-responsive drug delivery. Issue 15 (2nd April 2019) - Mei, Leixia; Xu, Keming; Zhai, Ziran; He, Suyun; Zhu, Tingting; Zhong, Wenying
Abstract : Doxorubicin reinforced the self-assembly of RGD-derived peptide conjugates responsive to mild acidity. Abstract : Drug incorporation in hydrogels often brings undesirable effects on the stability or mechanical properties of the system. To address this problem, we report the design and synthesis of a RGD-derived peptide conjugate (1-RGDH) for its co-assembly with a commonly used chemotherapeutic drug, doxorubicin (DOX), that formed electrostatic interactions with the 1-RGDH peptide and reinforced the supramolecular network of nanofibers within the matrix of the hydrogel. The hybrid hydrogel demonstrated excellent viscoelastic and shear-thinning properties that greatly facilitated the development of injectable drug delivery systems. Furthermore, it demonstrated a unique pH responsive release of DOX under weakly acidic conditions, paving ways for the controlled release of drug cargos in a typical tumor microenvironment with mild acidity. Finally, the DOX-incorporated hydrogel exhibited a superior anti-tumor efficacy in non-small-cell lung cancer cells A549 compared to the aqueous solution of free DOX, with an integrin receptor-mediated endocytosis pathway revealed for the cellular uptake of DOX-incorporated nanofibers.